2001
DOI: 10.1046/j.1432-1327.2001.01989.x
|View full text |Cite
|
Sign up to set email alerts
|

P‐Glycoprotein preferentially effluxes anthracyclines containing free basic versus charged amine

Abstract: The multidrug resistant (MDR) tumor phenotype, characterized by a decreased cellular drug accumulation is achieved by ATP-dependent extrusions of drugs from cells by P-glycoprotein (P-gp) and/or by multidrug resistance protein (MRP1). Despite the huge amount of research that has been performed on the mechanisms of P-gpmediated efflux of drug, it is not yet known what the molecular parameters are required for a molecule to be recognized and pumped out by P-gp. Anthracyclines are weak bases and, depending on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…However, it is the uncharged form of the drug which is transported via passive diffusion across the membranes (59), and it has also been shown that it is transported better by PGP than charged doxorubicin (21). Our data show a very similar location profile of neutral doxorubicin ( Figure 5B) compared to that for data acquired at pH 7.4 (see the Supporting Information).…”
Section: Discussionsupporting
confidence: 69%
“…However, it is the uncharged form of the drug which is transported via passive diffusion across the membranes (59), and it has also been shown that it is transported better by PGP than charged doxorubicin (21). Our data show a very similar location profile of neutral doxorubicin ( Figure 5B) compared to that for data acquired at pH 7.4 (see the Supporting Information).…”
Section: Discussionsupporting
confidence: 69%
“…For weakly basic therapeutics such as mitoxantrone, doxorubicin, and topotecan, the acidic extracellular environment in the tumor results in an accumulation of the charged species in the extracellular space and greatly decreases their efficacy [255,256]. Furthermore, the acidic microenvironment can also enhance the activity of known drug transporters such as p-glycoproteins and confer an additional mechanism of drug resistance through increased efflux [257,258]. However, the acidic tumor environment can also be exploited for therapeutic purposes.…”
Section: Acidic Tumor Microenvironmentmentioning
confidence: 99%
“…This would be expected to cause a shift toward the uncharged moiety of the drug, increasing binding to efflux transporters and reducing cellular drug concentration. Further confirmatory evidence comes from the work of Frezard et al, who suggested that the uncharged form of anthracycline (favored in alkaline conditions) is pumped out of cells more efficiently through P‐gp effluxors 36. Therefore, it seems that drug uptake and cytotoxicity are favored if an alkaline outside/acid inside pH gradient is present.…”
Section: Discussionmentioning
confidence: 86%